Collaboration technologies and social computing : 25th international conference, CRIWG+CollabTech 2019, Kyoto, Japan, September 4-6, 2019, proceedings /: 25th international conference, CRIWG+CollabTech 2019, Kyoto, Japan, September 4-6, 2019, proceedings. ([2019]) - Unknown
No abstract available